Atypical flavobacteria recovered from diseased fish in the Western United States - Heckman, Taylor I.; Yazdi, Zeinab; Pomaranski, Eric K.; Sebastião, Fernanda de Alexandre; Mukkatira, Kaveramma; Vuglar, Brent M.; Cain, Kenneth D.; Loch, Thomas P.; Soto, Esteban (Frontiers in Cellular and Infection Microbiology, 2023)
Flavobacterial diseases, caused by bacteria in the order Flavobacteriales, are responsible for devastating losses in farmed and wild fish populations worldwide. The genera Flavobacterium (Family Flavobacteriaceae) and Chryseobacterium (Weeksellaceae) encompass the most well-known agents of fish disease in the order, but the full extent of piscine-pathogenic species within these diverse groups is unresolved, and likely underappreciated. To identify emerging agents of flavobacterial disease in US aquaculture, 183 presumptive Flavobacterium and Chryseobacterium isolates were collected from clinically affected fish representing 19 host types, from across six western states. Isolates were characterized by 16S rRNA gene sequencing and phylogenetic analysis using the gyrB gene. Antimicrobial susceptibility profiles were compared between representatives from each major phylogenetic clade. Of the isolates, 52 were identified as Chryseobacterium species and 131 as Flavobacterium. The majority of Chryseobacterium isolates fell into six clades (A-F) consisting of ≥ 5 fish isolates with ≥ 70% bootstrap support, and Flavobacterium into nine (A-I). Phylogenetic clades showed distinct patterns in antimicrobial susceptibility. Two Chryseobacterium clades (F & G), and four Flavobacterium clades (B, G-I) had comparably high minimal inhibitory concentrations (MICs) for 11/18 antimicrobials tested. Multiple clades in both genera exhibited MICs surpassing the established F. psychrophilum breakpoints for oxytetracycline and florfenicol, indicating potential resistance to two of the three antimicrobials approved for use in finfish aquaculture. Further work to investigate the virulence and antigenic diversity of these genetic groups will improve our understanding of flavobacterial disease, with applications for treatment and vaccination strategies.